The relationship between the quality of the workforce and educational factors in Cibogo Village, Subang Regency - Dian Tiana; Hasvika Saviela; Oktavian Dwi Santoso (Universitas Pendidikan Indonesia, 2024)
This program examines the potential and challenges of Cibogo Village, Subang Regency's workforce during the Community Services Program (Kuliah Kerja Nyata or KKN) activities conducted by the Universitas Pendidikan Indonesia. Despite Cibogo Village having a significant workforce, particularly within the productive age range, disparities in the quality of the workforce are the primary focus. Data indicates that most of the workforce has only basic education, such as completing primary school or its equivalent, creating obstacles in meeting the demands of an increasingly developing industrial era. Additionally, there is an imbalance in job participation between men and women, with a significant number of women choosing to be homemakers. A descriptive approach with data collection through observation was used in this program. The results suggest the need for efforts to improve education and skills training to enhance the quality of the workforce in Cibogo Village. Furthermore, a deeper understanding of gender roles in job participation is essential to create equality and empowerment between men and women. Based on this, Cibogo Village can obtain an overview of its potential, mainly related to factors that can be of concern for improvement, especially in terms of gender equality, absorption of science and technology, and development of UMKMs. Abstrak Program ini mengkaji potensi dan permasalahan angkatan kerja di Desa Cibogo, Kabupaten Subang saat kegiatan Kuliah Kerja Nyata (KKN) Universitas Pendidikan Indonesia berlangsung. Meskipun Desa Cibogo memiliki jumlah angkatan kerja yang signifikan, terutama dalam rentang usia produktif, perbedaan kualitas angkatan kerja menjadi sorotan utama. Data menunjukkan bahwa sebagian besar angkatan kerja hanya memiliki pendidikan dasar, seperti tamat SD atau setara, sehingga menciptakan hambatan dalam memenuhi tuntutan pekerjaan di era industri yang semakin berkembang. Selain itu, terdapat ketidakseimbangan dalam partisipasi pekerjaan antara laki-laki dan perempuan, di mana sebagian besar perempuan memilih untuk menjadi ibu rumah tangga. Pendekatan deskriptif dengan pengumpulan data melalui observasi digunakan pada kegiatan ini. Hasil menunjukkan bahwa perlu adanya upaya peningkatan pendidikan dan pelatihan keterampilan untuk meningkatkan kualitas angkatan kerja di Desa Cibogo. Selain itu, perlu pemahaman lebih mendalam terkait peran gender dalam partisipasi pekerjaan agar dapat menciptakan kesetaraan dan pemberdayaan antara laki-laki dan perempuan di dunia kerja. Berdasarkan hal tersebut Desa Cibogo dapat memperoleh gambaran potensi desa, utamanya berkaitan dengan faktor-faktor yang dapat menjadi perhatian untuk ditingkatkan, khususnya dari sisi penyetaraan gender, penyerapan IPTEK dan pengembangan UMKM. Kata Kunci: Angkatan kerja; faktor pendidikan; kuliah kerja nyata